Identification and ultra‐high‐performance liquid chromatography coupled with high‐resolution mass spectrometry characterization of biosurfactants, including a new surfactin, isolated from oil‐contaminated environments. Issue 4 (14th May 2018) - Moro, Glaci V.; Almeida, Rafaela T.R.; Napp, Amanda P.; Porto, Carla; Pilau, Eduardo J.; Lüdtke, Diogo S.; Moro, Angélica V.; Vainstein, Marilene H.
Summary: Biosurfactant‐producing bacteria were isolated from samples collected in areas contaminated with crude oil. The isolates were screened for biosurfactant production using qualitative drop‐collapse test, oil‐spreading and emulsification assays, and measurement of their tensoactive properties. Five isolates tested positive for in the screening experiments and displayed decrease in the surface tension below 30 mN m −1 . The biosurfactants produced by these isolates were further investigated and their molecular identification revealed that they are bacteria related to the Bacillus genus. Additionally, the biosurfactants produced were chemically characterized via UHPLC‐HRMS experiments, indicating the production of surfactin homologues, including a new class of these molecules. Abstract : Biosurfactant‐producing bacteria isolated from areas contaminated with crude oil or its byproducts were screened and five out of two hundred isolates furnished significant decrease of surface tension below 30 mN m −1 . Bacillus amyloliquefaciens MO4B has shown to be a very promising biosurfactant producer, particularly due to its ability to efficiently reduce the surface tension. The biosurfactants produced were fully chemically characterized via UPLC‐HRMS, indicating the production of surfactin homologues, including a new member of this family is reported for the first time in the literature.